THE EFFECT OF “PANDAN PANTAI” LEAF FIBER ADDITION TO CONCRETE STRENGTH - Mawardi Mawardi (Universitas Bengkulu, 2019)
There are several fibers which can be used for improving concrete properties. Such as steel fiber, fiber glass, banana fiber. The objective of this research is to know how Pandan leaf fibers Beach affects to the concrete strength. During the experiment 2.5 mm fibers were mixed to the concrete mortar. The fiber length diameter was 0.2-0.5 mm. The concrete simple size is 15 cm x 15 cm x l60 cm. The cement water factor was 0.45 –0,6. The fiber volume proportion were 0%, 1%, 2%, and 3%.It was observed that those addition increase the strength by 18%, and decrease concrete breaks